Preferential oxidation of carbon monoxide in hydrogen-rich gases over supported cobalt oxide catalysts - Nyathi, Thulani Mvelo (Centre for Catalysis Research, 2016)
The preferential oxidation of CO (CO-PROX) has been identified as one route of further reducing the trace amounts of CO (approx. 0.5 - 1 vol%) in the H2-rich reformate gas after the high- and low-temperature water-gas shift reactions. CO-PROX makes use of air to preferentially oxidise CO to CO₂, reducing the CO content to below 10 ppm while minimising the loss of H₂ to H₂O. In this study, a Co₃O₄/γ-Al₂O₃ model catalyst was investigated as a cheaper alternative to the widely used noble metal-based ones. The CO oxidation reaction in the absence of hydrogen has been reported to be crystallite size-dependent when using Co₃O₄ as the catalyst. However, studies looking at the effect of crystallite size during the CO-PROX reaction are very few. Metal-support interactions also play a significant role on the catalyst's performance. Strong metal-support interactions (SMSI) in Co₃O₄/Al2o₃ catalysts give rise to irreducible cobalt aluminate-like species. Under CO oxidation and CO-PROX reaction conditions, such strong interactions in a similar catalyst can have a negative effect on the performance of Co₃O₄ but can keep its chemical phase intact i.e., help prevent the reduction of the Co₃O₄ phase. The catalysts used to investigate these two effects (i.e., crystallite size and metal-support interactions) were synthesised using the reverse micelle technique from which nanoparticles with a narrow size distribution were obtained. Certain properties of the microemulsions prepared were altered to obtain five catalysts with varying Co₃O₄ crystallite sizes averaging between 3.0 and 15.0 nm. Four other catalysts with different metal-support interactions were also synthesised by altering the method for contacting the support with the cobalt precursor. The crystallite size of Co₃O₄ in these four catalysts was kept in the 3.0 - 5.0 nm size range.